1979
DOI: 10.1128/aac.16.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic pathway leading to gentamicin C2b

Abstract: Incubation of Micromonospora purpurea SC 1210 (NRRL 5467) with L-[methyl-14C]methionine yielded [methyl-14C]gentamicin A and methyl-14C-labeled antibiotic JI-20A in a molar radioactivity ratio of 9:2. We did not isolate methyl-14C-labeled gentamicin X2, which was expected as an intermediate based on the biosynthetic pathways proposed by others. Addition of methyl-14C-labeled antibiotic JI-20A to M. purpurea SC 1124 (NRRL 8102) yielded [methyl-14C]-gentamicin C1a and [methyl-14C]gentamicin C2b in variable molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Furthermore, the step from gentamicin A to X2 , involving Cmethylation with epimerization at C-4", is also cobalt dependent (GRISEBACH 1978;TESTA and TILLEY 1979). Labeling experiments with L-[CH 3 -14 C]methionine indicated that the methyl groups in gentamicin were all derived from the methionine methyl (LEE et al 1973(LEE et al , 1975(LEE et al , 1976(LEE et al , 1979. Labeling experiments with L-[CH3-14C]-and L-[CH 3 -2 H] methionine simultaneously applied also supported the above conclusion (DANIELS et al 1976).…”
Section: Subunit Assemblysupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the step from gentamicin A to X2 , involving Cmethylation with epimerization at C-4", is also cobalt dependent (GRISEBACH 1978;TESTA and TILLEY 1979). Labeling experiments with L-[CH 3 -14 C]methionine indicated that the methyl groups in gentamicin were all derived from the methionine methyl (LEE et al 1973(LEE et al , 1975(LEE et al , 1976(LEE et al , 1979. Labeling experiments with L-[CH3-14C]-and L-[CH 3 -2 H] methionine simultaneously applied also supported the above conclusion (DANIELS et al 1976).…”
Section: Subunit Assemblysupporting
confidence: 70%
“…B.IV, the possibility of the formation of kanamycin A from kanamycin B by a similar substitution is suggested. e) Additional Findings on Biosynthesis LEE et al (1979) reported data contradictory to the above biosynthetic pathway for gentamicin. They found that the incubation of M.purpurea SC 1210, a producer of antibiotic JI-20A, with L-[CH r 14 C]methionine yielded [CH 3 -14 C]gentamicin A and [CH3-14C]JI-20A in a molar radioactivity ratio of 9:2.…”
Section: B) Studies On Sisomicin-producing Strainmentioning
confidence: 90%